Linearly-elastic three-layer plate in the acoustic medium - Ковалец, Ольга Яковлевна (Eastern-European Journal of Enterprise Technologies, 2010)
The analysis is conducted and the nature of resilient interaction of the three-layered plate with a flat monochromatic wave of superfluous pressure of sound frequency is studied. Within the limits of one-dimensional problem the law of flexural motion of barrier is determined.